Telephone Encounters Predict Future High Financial Expenditures in Inflammatory Bowel Disease Patients: A 3-Year Prospective Observational Study. Issue 4 (April 2018) - Click, Benjamin; Anderson, Alyce M.; Ramos Rivers, Claudia; Koutroubakis, Ioannis E.; Hashash, Jana G.; Dunn, Michael A.; Schwartz, Marc; Swoger, Jason; Barrie, Arthur; Szigethy, Eva; Regueiro, Miguel; Schoen, Robert E.; et al.
Abstract : Background: Telephone activity is essential in management of complex chronic diseases including inflammatory bowel disease (IBD). Telephone encounters logged in the electronic medical record have recently been proposed as a surrogate marker of disease activity and impending health care utilization; however, the association between telephone calls and financial expenditures has not been evaluated. Study: We performed a 3-year prospective observational study of telephone encounters logged at a tertiary referral IBD center. We analyzed patient demographics, disease characteristics, comorbidities, clinical activity, and health care financial charges by telephone encounter frequency. Results: Eight hundred one patients met inclusion criteria (52.3% female; mean age, 44.1 y), accounted for 12, 669 telephone encounters, and accrued $70, 513, 449 in charges over 3 years. High telephone encounter frequency was associated with female gender ( P =0.003), anxiety/depression ( P <0.001), and prior IBD surgery ( P <0.001). High telephone encounter categories had significantly more hospitalizations ( P <0.001), IBD surgery ( P <0.001), worse quality of life ( P <0.001), more corticosteroid ( P <0.001), biological ( P <0.001), and opiate prescriptions ( P <0.001). High telephone encounter frequency patients amassed higher total available charges in each year ( P <0.001) and over the 3 years ( P <0.001). Telephone encounters in 2009 ( P =0.02) and 2010 ( P <0.001) were significantly associated with financial charges the following year after controlling for demographic, utilization, and medication covariates. Conclusions: Increased telephone encounters are associated with significantly higher health care utilization and financial expenditures. Increased call frequency is predictive of future health care spending. Telephone encounters are a useful tool to identify patients at risk of clinical deterioration and large financial expense. Abstract : Supplemental Digital Content is available in the text.